Analysis of the Relationship Between Children's Characteristics, Family Characteristics, Food Intake, Eating Habits, and Disease History with Nutritional Status of Under-Five Children Based on the Composite Index of Anthropometric Failure in Karangkamulyan Village, Cihara District, Lebak Regency, Indonesia in 2020 - Ayu Anisadiyah; Ratu Ayu Dewi Sartika (Indonesian Journal of Public Health Nutrition, 2022)
Composite Index of Anthropometric Failure (CIAF) is an indicator of composite nutritional status assessment (WAZ, HAZ, and WHZ) to describe toddler's nutritional problems. In 2020, malnutrition, unemployment, and poverty in Banten Province were high, the population's income tends to be low. Karangkamulyan is an underdeveloped village with mining areas. This is a secondary study used a cross-sectional study design to analyze the relationship between children's characteristics, family characteristics, food intake, eating habits, and disease history with the toddler's nutritional status based on CIAF in Karangkamulyan Village in 2020. The primary research was conducted in September 2020, instrument used is a questionnaire. The sample was 141 toddlers aged 24-59 months. Data were analyzed by univariate and bivariate. The results found that children under five experienced nutritional problems were 36.2%. The variables related to toddler's nutritional status, is exclusive breastfeeding (p=0.026), energy intake (p=0.026), and vegetable protein consumption habits (p =0.003).